Post-Peak China in Africa? - Carmody, Padraig (Afrika Tanulmányok / Hungarian Journal of African Studies, 2023)
China’s increased engagements in Africa over the past two decades have been as notable as they have been controversial. While some have predicted China’s economic stagnation as a result of issues such as debt, supply chain shortening as a result of the impacts of COVID and the impact of strict lockdowns in that country, others see its economy dramatically rebounding. However, it appears that Chinese lending to Africa has now peaked and is in precipitous decline. Other indicators of economic engagement have also decreased and other powers are also now vigorously contesting for space on the continent. This paper examines whether or not we are now in a period “post-peak China in Africa” and the reconfiguration of strategies of influence. The original Ian Taylor Memorial Lecture under the same title held on April 27, 2023 at the University of Pécs has been edited and headings added for clarity, and references included/provided.